Level of technical-tactical performance and sports experience of athletes of volleyball in the categories of formation - Margareth Porath; Juarez Vieira do Nascimento; Michel Milistetd; Carine Collet; William das Neves Salles; Ricardo Teixeira Quinaud (Revista da Educação Física, 2013)
The aim of this study was to evaluate the technical and tactical performance of volleyball players and compare them according to their experience level in sport. Twenty-four teams finalists in the 2010 State Championship of Santa Catarina in categories under-15, under-16 and under-17 have participated in the study. The instruments used were a questionnaire to athletes to identify the level of sport experience and Technical-Tactical Evaluation Tool in Volleyball (IAD-VB) by Collet et al. (2011) to evaluate the technical-tactical actions. For data analysis we used descriptive statistics and multinomial logistic regression, in the SPSS software, adopting the significance level p <0.001. The results indicated that the category under-15 had no relationship between technical and tactical performance of players and experience in the sport, confirming the assumptions of a long-term sports development. The sports experience has favored the technical and tactical development of young volleyball players, especially in the categories under-16 and under-17.